Les Jeunes Tunisiens, une contre-expérience de la minoration ? Politisation des langues dans la presse francophone en Tunisie coloniale (1907-1912) - Sarra Zaïed (L’Année du Maghreb)
Les Jeunes Tunisiens (the Young Tunisians) laid the groundwork for a mobilisation of the political landscape of colonial Tunisia at the beginning of the 20th century. As a bilingual elite, mastering Arabic and French, they defined themselves as natural intermediaries, spokespersons for Tunisians in the colonial situation. They were nevertheless challenged by their French contemporaries. This article questions the idea that bilingualism is an essential asset to get out of a situation of undermining, and is part of what the historian Hassine Raouf Hamza has called “post-national history”, showing the richness of Tunisian political life without limiting it to a single “national movement”, by examining the rise of the Young Tunisians in another way. The article therefore questions this bilingual elite through the prism of its discourse vis-à-vis the preponderant discourse, thereby going beyond simply studying them through the prism of their nationalist actions. The stakes of bilingualism are captured here through the press. The press in colonial Tunisia developed at the beginning of the 20th century, and periodicals, in Arabic or French, were an essential part of political life. Gradually, the political positions taken in these periodicals transformed the press into a “combat press” (Julien, 1967). Through the study of two French-language periodicals with opposite points of view, I examine the way in which the language of the press is transformed through contact with other periodicals. The dialogical dimension (Bakhtine, 1978) of the speeches published in Le Tunisien, the organ of the Young Tunisians, and in Le Colon français, the organ of the “prépondérants” (French colonial lobby), reflects the richness of the exchanges and debates in Tunisia at the beginning of the century. This was a turning point in the history of colonial Tunisia, and these speeches appeared at a time of debate, particularly in metropolitan France, on the conditions and terms of colonisation. Thus, each party tried to undermine its political opponent, giving rise to rich and antagonistic exchanges. In addition, the Young Tunisians tried to escape the status of minimisation acquired during the establishment of the protectorate, and to reactivate a symbolic place in their speeches in the press. In this perspective, they put into place strategies to escape minoritisation. Thus, I propose to shed light on a strategy that has not yet been explored in the historiography of Tunisian nationalism, namely, the politicisation of language, and of bilingualism in particular. The Young Tunisians, faced with the diatribes launched by Le Colon français, positioned themselves as authority figures in colonial Tunisia by making knowledge of French and Arabic essential conditions for participation in Tunisian political life. The Young Tunisians made their linguistic competence – their French/Arabic bilingualism – a statutory competence (Bourdieu, 1982), thus negotiating their place as intermediaries in the Francophone press. In a way, this article revisits the concept of “dominant language” (Calvet, 1974) and provides another perspective on the importance of French in colonial and post-colonial Tunisia. The French language was taken up by the Young Tunisians as a privileged tool in order, on the one hand, to make it an instrument of mobilisation and, on the other, to escape their undermining. The status of the language was based on Tunisian actors who needed French to act as intermediaries and to occupy official positions within the colonial administration. This analysis therefore allows us to qualify the concepts of “dominant language” and “dominated language” and to show the dialogue between two languages among a literate elite.